2005
DOI: 10.1016/j.icesjms.2005.03.001
|View full text |Cite
|
Sign up to set email alerts
|

The role of mixotrophy in plankton bloom dynamics, and the consequences for productivity

Abstract: . W. 2005. The role of mixotrophy in plankton bloom dynamics, and the consequences for productivity. e ICES Journal of Marine Science, 62: 833e840.Mixotrophy (Zheterotrophy and photosynthesis by a single individual) is a common phenomenon in aquatic ecosystems, in particular under light-or nutrient-limitation. However, it is not usually considered in mathematical models of biological populations. This paper shows how different types of mixotrophy might be usefully incorporated into a general predatoreprey mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(37 citation statements)
references
References 28 publications
2
35
0
Order By: Relevance
“…Two modeling studies determined that primarily heterotrophic mixotrophs can have a great effect on primary production, and that this type of mixotrophy can lead to a noticeable increase in primary production even at 1% of the population (Stickney et al 2000, Hammer & Pitchford 2005. Determining the quantitative contributions of phagotrophy and phototrophy was beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 96%
“…Two modeling studies determined that primarily heterotrophic mixotrophs can have a great effect on primary production, and that this type of mixotrophy can lead to a noticeable increase in primary production even at 1% of the population (Stickney et al 2000, Hammer & Pitchford 2005. Determining the quantitative contributions of phagotrophy and phototrophy was beyond the scope of our study.…”
Section: Discussionmentioning
confidence: 96%
“…Mitra and Flynn (2010) have indeed shown that descriptions integrating physiological processes, with some degree of feedback to modulate the processes of phototrophy and heterotrophy, are needed to properly represent the qualitative behavior of mixotrophs. Among existing mixotrophic models, only those of Stickney et al (2000) and the "perfect beast" of Flynn and Mitra (2009) take the interactions between the two trophic modes into account; the others rely on additive descriptions of phototrophy and heterotrophy (Thingstad et al, 1996;Baretta-Bekker et al, 1998;Jost et al, 2004;Hammer and Pitchford, 2005;Crane and Grover, 2010;Ward et al, 2011;Våge et al, 2013).…”
Section: Non-constitutive Mixotrophymentioning
confidence: 99%
“…Most interest has been leveled at the potential impact of mixotrophs on the microbial food web structure and functioning, and the conditions under which mixotrophs may likely coexist with strict phototrophs and heterotrophs (Thingstad et al, 1996;BarettaBekker et al, 1998;Stickney et al, 2000;Jost et al, 2004;Hammer and Pitchford, 2005;Hood et al, 2006;Flynn and Mitra, 2009;Crane and Grover, 2010;Ward et al, 2011;Våge et al, 2013). By far the greater effort has been applied to CM organisms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Following these efforts, and with increased awareness of mixotrophy as a nutritional strategy among many planktonic species, modelers began to investigate the consequences of different forms of mixotrophy, as described above (11), including elemental stoichiometric considerations of prey and nutrient availability (12). Subsequent mathematical analyses revealed that the inclusion of mixotrophy in models could affect the equilibrium community structure and improve stability of the biological community (13,14). This early work envisioned mixotrophs as constituitively photosynthetic organisms (i.e., predatory phytoflagellates).…”
mentioning
confidence: 99%